EFFECTIVENESS OF CASE-BASED LEARNING COMPARED TO LECTURES AND TUTORIAL SESSIONS IN MEDICAL EDUCATION: GENDER AND CLINIC BASED PERSPECTIVES - Ahmed, Mamoon; Imam, Kamil Asghar; Rehman, Muneebur; Malik, Ahmed Hassaan (Pakistan Journal of Physiology, 2016)
Background: Trends in medical education have shifted away from didactic teaching and towards contextual or problem-based learning (PBL). Our study attempted to explore effectiveness of case-based learning (CBL) sessions in medical education when compared to traditional lecture based learning and tutorial sessions based on gender and pre-clinical/clinical years of undergraduate medical education. Methods: This study was carried out at Army Medical College, National University of Medical Sciences (NUMS), Rawalpindi, Pakistan from 15th Dec 2012 to 20th Feb 2013. Participants of the study included 500 randomly selected undergraduate medical students of pre-clinical/clinical years. A questionnaire investigating six different aspects of CBL was distributed among 2nd, 3rd, 4th and 5th year students. Fifty male and 50 female students were included from 2nd and 3rd year, while 75 male and 75 female students were included from 4th and final year. Results: Feedback was received from 466 out of 500 (93.2%) students. Male students exhibited general trend of better adapting to CBL sessions compared to female students. There was skewed response on the basis of pre-clinical/clinical years of undergraduate medical education. Conclusions: Although all students were inclined towards CBL as a better learning option, male students had more positive opinion regarding all six aspects of case-based learning included in questionnaire of present study. Furthermore, clinical students regarded CBL as more effective tool of learning as compared to pre-clinical students. Students in pre-clinical years ranked CBL higher for ‘evoking creativity’, ‘favouring small group discussions’, and ‘strengthening interpersonal skills’ while clinical students rated CBL higher for ‘inducing problem solving capacity’, ‘providing proper attention of facilitator’ and ‘providing hands-on approach’. Pak J Physiol 2016;12(1):42–6